Uji Dan Penetuan Efek Ekstrak Putik Sawo (Manilkara zapota L.) Terhadap Penyembuhan Luka Sayat Pada Mencit Putih Jantan - Muhajri Agusfina; Kevin Julio (Journal Pharma Saintika, 2022)
Research has been carried out to test and determine the effects of ethanol extract of sapodilla pistil (Manilkara zapota L.) on the healing of cuts in male white mice. From the statistical tests that have been carried out, it results that the data is normally distributed which is calculated using the Liliford test, while the ANOVA test shows no significant difference between the test substance groups at 5% concentration, 10% concentration and 20% concentration, with the conclusion that the ethanol extract of sapodilla pistil has an effect on the healing of cuts and accelerates the healing of cuts at a concentration of 5% compared to 10% and 20%.